FAKTOR-FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KONSENTRASI COHb DALAM DARAH PADA PETUGAS PARKIR MALL DI KOTA SEMARANG - Kanthi Hidayahsti; Mursid Rahardjo; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Carbon monoxide is a dangerous pollutant because it is highly toxic to humans. Construction of Mall in the Semarang city is always included with the construction of parking buildings. The parking location into one of the contaminated CO due to the activity of a motor vehicle may harm the health of workers in it. This study aimed to determine risk factors related to COHb concentrations in the blood of mall parking attendant in Semarang city. This type of research was observational with cross sectional approach. The population in this study was the air in the parking environment and 76 parking attendant. Samples from this study were located at 14 locations of air samples with the number of respondents 43 people with simple random sampling method. The results of the measurement of CO concentration in the Mall parking area is in the range 2.20 to 19.40 ppm. COHb concentration in the blood of Mall parking workers at the Semarang most have COHb concentrations in the blood is not normal (≥2%) in the amount of 65.1% (28 respondents).The results of test Chi square test shows that there are correlation in smoking habits (p = 0.019) with a COHb concentration in the blood as well as their habit of smoking, is a risk factor with the COHb concentration in the blood (RP = 6.000). The conclusion of this study are there is have a relationship of smoking habits with COHb concentrations in the blood of the mall parking workers in the Semarang city.